Charvátská Nová Ves, Tschechische Republik: Ein temporäres römisches Militärlager in Südmähren - Hüssen, Claus-Michael; Komoróczy, Balázs; Vlach, Marek (e-Forschungsberichte des DAI, 2023)
The research on the Roman camp of Charvátská Nová Ves in Moravia took place within the framework of a cooperative project on the study of military activities during the period of the Marcomannic wars (bellum Germanicum et Sarmaticum) north of the Pannonian Danube frontier in the reign of Emperor Marcus Aurelius (166–180 AD). With archaeological and scientific methods, temporary camps from the Roman campaigns were examined within the context of the Germanic settlements. The fieldwork in 2013–2014 focused on the camp in Charvátská Nová Ves, which was discovered in the early 1990s. With an inner surface of just over 40 hectares, it is the largest temporary camp west of the Little Carpathians and provided space to a field army of more than 10,000 legionaries.